PENGARUH EASE OF DOING BUSINESS DAN BUSINESS CONFIDENCE TERHADAP GLOBAL COMPETITIVENESS INDEX (Studi pada Negara Amerika Serikat, China, dan Indonesia Tahun 2005 – 2017) - Dhira Aditya Nanda; Suhadak Suhadak (Jurnal Administrasi Bisnis, 2018)
The purpose of this research is to know and explain the ease of doing business to business confidence, to know and explain the ease of doing business against global competitiveness index, the last is to know and explain the influence of business confidence on global competition index. The results of research in United States indicate that there is no influence between ease of doing business with business confidence and business confidence with global competitiveness index. But, there is an influence between ease of doing business with global competitiveness index. The result of research in China shows that there is no influence between ease of doing business with business confidence and business confidence with global competitiveness index. But, there is an influence between ease of doing business with global competitiveness index, and there is no influence between The result of the research in Indonesia shows that there is no influence between ease of doing business with business confidence and business confidence with global competitiveness index. But, there is an influence between ease of doing business with global competitiveness index.  Kеywords: Ease of Doing Business, Business Confidence, Global Competitiveness Index АBSTRАK Tujuan penelitian ini adalah  untuk mengetahui dan menjelaskan pengaruh ease of doing business terhadap business confidence, mengetahui dan menjelaskan pengaruh ease of doing business terhadap global competitiveness index, mengetahui dan menjelaskan pengaruh business confidence terhadap global competitveness index. Hasil penelitian pada Negara Amerika Serikat menunjukkan bahwa tidak terdapat pengaruh antara ease of doing business dengan business confidence, terdapat pengaruh antara ease of doing business dengan global competitiveness index, dan tidak terdapat pengaruh antara business confidence dengan global competitiveness index. Hasil penelitian pada Negara China menunjukkan bahwa tidak terdapat pengaruh antara ease of doing business dengan business confidence, terdapat pengaruh antara ease of doing business dengan global competitiveness index, dan tidak terdapat pengaruh antara business confidence dengan global competitiveness index. Hasil penelitian pada Negara Indonesia menunjukkan bahwa tidak terdapat pengaruh antara ease of doing business dengan business confidence, terdapat pengaruh antara ease of doing business dengan global competitiveness index, dan tidak terdapat pengaruh antara business confidence dengan global competitiveness index. Kаtа Kunci: Ease of Doing Business, Business Confidence, Global Competitiveness Index